The diverse impacts of extreme storms in the European South. The case of StormDaniel(2023) in Greece - Diakakis, M.; Mavroulis, S.; Filis, Christos; Bantekas, Yiannis; Marilia Gogou; Katsetsiadou, Katerina-Nafsika; Mavrouli, Maria; Giannopoulos, Vasilis; Sarantopoulou, Andromachi; Nastos, Panagiotis; Vassilakis, Emmanuel; Konsolaki, Aliki; et al. (EGUGeneral Assembly 2024, 2024)
On September 4, 2023, Storm Daniel moved inland from the Ionian Sea, intensifying due to the warmth of the post-summer Mediterranean Sea, resulting in intense rainfall and thunderstorms over the Balkans. Central Greece was particularly affected, experiencing the highest daily rainfall totals recorded in the region.The storm caused widespread devastation, especially in the Thessaly region, with significant impacts including intense erosion, mass movement phenomena triggered by rainfall, damages from strong winds, inundation, agricultural land damage, loss of life and injuries, impacts on residences and businesses, as well as a substantial toll on the environment and cultural sites.This study focuses on Storm Daniel and its effects in Thessaly, Greece, by creating a database of distinct impact elements based on field surveys and public records. Through this archive, the study explores the range of its impacts, developing a systematic categorization to provide an in-depth understanding of the types and mechanisms of these impacts.Examining extreme storms through post-flood surveys and emphasizing their impacts can enhance our comprehension of associated risks. This knowledge will facilitate more accurate predictions and strategic planning for such events, contributing to improved emergency management and recovery efforts. Anticipating the impacts becomes crucial, particularly in the context of the projected increase in the frequency of such events due to climate change, thereby strengthening our preparedness.